The Effect of Government Expenditure, Unemployment, and Inflation on Economic Growth in Denpasar City from 2004 to 2023 - Ida Ayu Sri Nanda Atasya; Ida Bagus Putu Purbadharmaja (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the influence of government expenditure, unemployment, and inflation on the economic growth of Denpasar City from 2004 to 2023. The independent variables include government expenditure, unemployment, and inflation, while the dependent variable is economic growth. This research utilizes secondary data obtained from the Bali Province Central Bureau of Statistics (BPS). The results indicate that government expenditure, unemployment, and inflation simultaneously have a significant effect on the economic growth of Denpasar City. Partially, government expenditure and unemployment have a negative and significant effect, whereas inflation has a positive but not significant effect on economic growth in Denpasar City.